Bioinspired grafting of peptide and NH2-AO to construct antifouling fiber membranes for fast uranium recovery from wastewater and seawater. (December 2022) - Li, Bochen; Wang, Yuefei; Xiao, Guoping; Shi, Se; Zhao, Peiqi; Feng, Ruxi; Zhang, Haiquan; Yuan, Yihui; Wang, Hui; Liu, Tao; Zhang, Ruizhi; Wang, Ning
Abstract: Uranium is an important nuclear element, and its efficient recovery is of great significance to nuclear industry and to nuclear safety. Herein, we rationally design robust antifouling fiber membranes (Anti-NH2 -AO FMs) by facilely grafting two novel ligands on porous surfaces. The efficient ligands, i.e., NH2 -AO and GSH, endow the membranes with rapid U-capture rate, good hydrophilicity and antifouling ability. Anti-NH2 -AO FMs display porous fiber network structure, good flexibility, and high mechanical strength (9.0 MPa). The uranium capture rate reaches up to 167 mg g −1 h −1 in the first two hours, and they can reduce uranium to 11 ppb in 2 ppm uranium-contaminated water, which is below the drinking water limit. Furthermore, Anti-NH2 -AO FMs still exhibit very high seawater permeability (6186 L m −2 h −1 bar −1 ) and flux recovery ratio (95.12 %) after three seawater fouling cycles. The imaging tests visually demonstrate their antiadhesion to the bacteria. In addition, they have good selectivity and long service life (10 cycles of adsorption-desorption). Kinetics models and XPS analyses illustrate the uranium adsorption mechanisms. Compared with the current membranes and fibers, the Anti-NH2 -AO displays the advantages of exceptional properties and easy preparation, and we believe that it possesses great potential in the practical uranium recovery. Graphical abstract: Unlabelled Image Highlights: An anti-adhesive fiber membrane is constructed by using the NH2 -AO and peptide. The NH2 -AO supplies the adsorbents with a very rapid uranium capture rate. The peptide endows the adsorbents with good seawater flux and antifouling ability. The membranes exhibit porous structure, flexibility, and high mechanical strength. The membranes have potential in the practical applications.